2020
DOI: 10.1074/jbc.ra119.012012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular dissection of the oxysterol-binding protein cycle through a fluorescent inhibitor

Abstract: ORPphilins are bioactive natural products that strongly and selectively inhibit the growth of some cancer cell lines and are proposed to target intracellular lipid-transfer proteins of the oxysterol-binding protein (OSBP) family. These conserved proteins exchange key lipids, such as cholesterol and phosphatidylinositol 4-phosphate (PI(4)P), between organelle membranes. Among ORPphilins, molecules of the schweinfurthin family interfere with intracellular lipid distribution and metabolism, but their functioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 34 publications
5
29
0
Order By: Relevance
“…At MCS between trans‐Golgi network (TGN) and endoplasmic reticulum (ER) (Mesmin et al , 2013), or between the lysosome and ER (Lim et al , 2019), oxysterol‐binding protein (OSBP) mediates the transport of PtdIns4P down its concentration gradient to the ER, fueling the countertransport cycle of cholesterol against its steep concentration gradient (Mesmin et al , 2013). This cholesterol/PtdIns4P exchange contributes to the establishment of a cholesterol gradient between organelles of the secretory pathway and is essential for protein trafficking to the plasma membrane (PM) (Péresse et al , 2020) and mTORC1 recruitment to lysosomes (Lim et al , 2019). At ER‐TGN MCS, PI4KIIα and PI4KIIIβ, as well as an ER PtdIns4P phosphatase (SAC1), maintain the TGN PtdIns4P gradient to perpetuate this exchange cycle (Mesmin et al , 2013; Zewe et al , 2018; Mesmin et al , 2019; Venditti et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…At MCS between trans‐Golgi network (TGN) and endoplasmic reticulum (ER) (Mesmin et al , 2013), or between the lysosome and ER (Lim et al , 2019), oxysterol‐binding protein (OSBP) mediates the transport of PtdIns4P down its concentration gradient to the ER, fueling the countertransport cycle of cholesterol against its steep concentration gradient (Mesmin et al , 2013). This cholesterol/PtdIns4P exchange contributes to the establishment of a cholesterol gradient between organelles of the secretory pathway and is essential for protein trafficking to the plasma membrane (PM) (Péresse et al , 2020) and mTORC1 recruitment to lysosomes (Lim et al , 2019). At ER‐TGN MCS, PI4KIIα and PI4KIIIβ, as well as an ER PtdIns4P phosphatase (SAC1), maintain the TGN PtdIns4P gradient to perpetuate this exchange cycle (Mesmin et al , 2013; Zewe et al , 2018; Mesmin et al , 2019; Venditti et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Such inhibition of OSBP led to a roughly fourfold increase in PI4P levels at the TGN and a roughly twofold increase in whole cells. A recent study using a different inhibitor also reported a similar effect ( Péresse et al, 2020 ). These data suggest the physiological contribution of OSBP in the regulation of PI4P and cholesterol at the TGN.…”
Section: Lipid Transport By Orps At Membrane Contact Sitesmentioning
confidence: 53%
“…Despite many previous studies, the mechanism of action by which schweinfurthins elicit cytotoxicity is poorly understood, and a molecular target has not yet been identified. Thus far, these compounds have been implicated in: oxysterol binding protein activity, lipid profiles, disruption of the Golgi and endoplasmic reticulum, and cholesterol trafficking, among other processes 2 , 13 18 . Schweinfurthins have been repeatedly shown to be highly toxic to some cell lines, such as SF-295 glioma cells, but well tolerated by others, including the A549 lung cancer cell line.…”
Section: Introductionmentioning
confidence: 99%